Complex Treatment and Identification Markers of Perimenopausal Osteoporosis - A. B. Nazarova (Research Journal of Trauma and Disability Studies, 2024)
A substantial proportion of the population of females in India falls in the perimenopausal and postmenopausal age groups. One of the complications associated with older age in women is the weakening of bones and the fall in bone mineral density (BMD). This has a severe debilitating consequence in a woman’s life and leads to reduced quality of life along with a greater incidence of fractures. If the fracture involves the hip or the vertebrae, it can cause immobility and be devastating. Postmenopausal osteoporosis is linked with the deficiency of estrogen that occurs with the cessation of the function of the ovaries as age progresses. The function of estrogen in the bone remodeling process is very well understood after years of research; estrogen plays a part in both the formation of bone as well as the prevention of the resorption of bone.